PELAKSANAAN PRAKTEK MENGAJAR BAGI GURU PESERTA PENDIDIKAN JARAK JAUH YANG TINGGAL DI WILAYAH TERPENCIL - Wahyuni Kadarko; Settings Dian Novita; Refni Delfi (Jurnal Pendidikan, 2010)
This study aims to identify problems facing by participants in experiencing teaching pratice under The Strengthening Teaching Competency Programme. An evaluation method was employed through problem and issues maping, interpreting problem dynamics, and improving actions. A qualitative-naturalistic approach with inteview was conducted during April-July 2009 to participants of Lower Secondary School Teacher Training who live in remote and rural areas in Bandung, Bogor and Serang region. Interview was also conducted to tutors, supervisors, programme manager, remote-school principals, peer teachers and students involved in the teaching practicum/exercise. Observations and documentary study were employed to support the data of the interview. Problems identified as the low performance of supervisory officials and partnership schools in guiding student teachers in developing didactic materials for both practicum and final exam. Most participants become stressed due to the absence of a definite timetable guidance process both in the process of lesson plan development, implementation of practicum and execution of final exams. It was suggested to redesign the current system with a more reliable system for participants coming from remote areas who wish to carry out teaching practice.